An early predictive model for Kawasaki disease shock syndrome in children in central China - Wu, Yali; Yin, Wen; Wen, Yini; Chen, Jing; Tang, Hongxia; Ding, Yan (Frontiers in Cardiovascular Medicine, 2024)
To analyze the clinical characteristics of Kawasaki disease shock syndrome (KDSS) and explore its early predictive factors. In this study, a retrospective case-control study method was used, and 28 children with KDSS and 307 children who did not progress to KDSS were included according to matching factors. Baseline information, clinical manifestations and laboratory indicators were compared between the two groups, and indicators of difference were analyzed on the basis of univariate analysis, and binary logistic regression analysis was used to discover risk factors for KDSS, followed by ROC analysis. A new scoring system was finally established: NLR ≥7.99 (6 points), FIB ≤5.415 g/L (1 point), Na ≤133.05 mmol/L (3 points), and a total score of ≥3.5 points were the high-risk factors for the progression to KDSS; otherwise, they were considered to be lowrisk factors. Consequently, as well as children with two or more of these risk factors are more likely to progress to KDSS, which helps in early clinical diagnosis and treatment.